Laboratory markers of osteosarcopenic obesity - O. V. Gritsenko; O. V. Gruzdeva; G. A. Chumakova; O. L. Barbarash (Российский кардиологический журнал)
Osteosarcopenic obesity syndrome involves the simultaneous deterioration of bone, muscle, and excess fat accumulation, resulting in systemic metabolic dysregulation. Currently, the relevance of this problem is increasing due to the global population aging, the high incidence of obesity, type 2 diabetes, sarcopenia and frailty in developed countries of the modern world. In this regard, novel diagnosis methods for this condition, including laboratory markers, should be developed. The review examines modern biomarkers of osteosarcopenic obesity.